Enhancing Organizational Performance: The Role of Corporate Culture, Leadership, and Employee Behavior in Policing - Modise, Dr. John Motsamai (The Informed Leader: How Philosophy and Evidence Shape Organizational Performance, 2025)
A company's organizational culture can be thought of as a collection of values, precepts, assumptions, and communication patterns that develop through time and enable the development of a particular functional psychological and social environment that supports the company's product offerings. To improve organizational performance, organizational management can, however, alter the organizational culture as required. This article sought to increase performance through corporate culture in policing, leadership, and employee behavior. The first element focuses on how well an organization performs in creating a high-performance culture that fosters excellence, high performance, and an environment of continuous improvement. The second area of attention is on leadership and how well an employer can influence and persuade people to work with him as a team to accomplish a specific objective. Although each leader has their own leadership style, it cannot be inherited automatically. Every leader possesses particular traits that manifest in various circumstances. The final section of the paper focused on the organizational culture of the Police, a unique type of law enforcement agency that ensures both internal order and public safety. The police simultaneously maintain the legal and structural security of the economy as an armed law enforcement agency. Security is crucial for both profit-making and non-profit enterprises, as well as for individuals and social organizations. The discussion on organizational culture further delves into different aspects like values, norms, and cultural forms, which are present in all organizational practices and activities. The values, beliefs, and attitudes created by organizational culture increase employees' commitment to the strategy and goals. It is a strategy that has the potential to boost an organizations’ productivity and give it a competitive edge. The study also discussed Organizational Citizenship Behavior, which refers to voluntary personal actions that are independent of the pay structure and contribute to improving an organization's efficiency. Job satisfaction and commitment represent antecedents of OCB, denoting a willingness to cooperate. The study concluded that the culture of the company has a significant impact on how well employees perform and how productive they are. The success of task performance reinforces OCB, which is a significant individual contribution that goes above and beyond the requirements of the function in the workplace. The study also recommended promoting team cohesion, establishing open lines of communication and setting clear, consistent goals.